Reflection on Teaching Asset Evaluation Cases Based on Framework Content - Li , Chang'an; Fang, Ying; Zheng, Qi (International Journal of Global Economics and Management, 2023)
This article aims to teach asset valuation case studies, focusing on the content of the asset valuation framework, and analyzing the significance, mode, and related issues of asset valuation case studies through practical experience, in order to provide reference opinions for improving asset valuation case studies.